Relationship of Low Income to Backlog in Kolaka Regency, Southeast Sulawesi Province - Gunawansyah, Gunawansyah; Hidayat, Arman; Machmud, Machmud; Sukman, Sukman; Amir, Andi Ahdan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The increasing population growth caused the government to launch the One Million Houses Program. The purpose of this study is to determine the relationship of low income to the backlog that occurs. From the results of the data survey conducted, it shows that the backlog of houses in Kolaka Regency in 2015 was 22,925 units that needed houses, while in 2020 there were 11,090 housing units which showed that there were still 48.37% from 2015.